Pemanfaatan Media Pembelajaran Adaptif di Kelas Inklusi - Hartina Rastam; Jesi Alexander Alim; Zetra Khainul Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe inclusive learning strategies for students with special needs in primary schools. The research employed a qualitative approach using field research methods. The study was conducted at SD Negeri 146 Pekanbaru, a school that has implemented inclusive education and accepted students with special needs for several years. The findings indicate that the implementation of inclusive education at SD Negeri 146 Pekanbaru demonstrates a strong commitment to accommodating the learning needs of all students. The strategies applied include the use of adaptive learning methods, the active role of special education teachers (GPK) in supporting classroom learning, and collaboration among teachers, parents, and school administrators. This collaborative approach creates a supportive and inclusive learning environment that fosters both academic and social development for every student.